2016
DOI: 10.1093/mnras/stv2896
|View full text |Cite
|
Sign up to set email alerts
|

X-ray timing analysis of the quasar PG 1211+143

Abstract: We report on a timing analysis of a new ∼630 ks XMM-Newton observation of the quasar, PG 1211+143. We find a well-defined X-ray power spectrum with a well-detected bend at ∼7 ×10 −5 Hz, consistent with the established t bend -M BH correlation for luminous, accreting black holes. We find the linear rms-flux relation commonly observed in accreting black hole systems and investigate the energy-dependence of the rms. The fractional rms is roughly constant with energy on short timescales (< 1 day; within observatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Indeed, as shown by Lobban et al (2016a), the spectral variability of PG 1211+143 is dominated by changes in the soft X-ray band.…”
Section: Outflow Variabilitymentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, as shown by Lobban et al (2016a), the spectral variability of PG 1211+143 is dominated by changes in the soft X-ray band.…”
Section: Outflow Variabilitymentioning
confidence: 82%
“…In Figure 2, the soft-band light curve is placed into the context of a longer ∼2 month monitoring campaign that we obtained with Swift (Gehrels et al 2004), where we have overlaid the observed 0.4-2 keV XMM-Newton EPIC-pn and Swift XRT count rates. The broadband XMM-Newton and Swift variability is described in Lobban et al (2016a), and we return to the soft-band spectral variability of PG 1211+143 later in Section 4. Our initial aim is to build a template model based on the mean spectrum of PG 1211+143 from the 2014 RGS observations, which then can be applied to all seven sequences (listed in Table 1) to study the variability of the fast soft X-ray wind.…”
Section: Mean Spectral Analysismentioning
confidence: 99%
“…We generated a set of self-consistent custom-built XSTAR grids with the correct ionizing continuum for PG 1211+143, based on a spectral energy distribution model described in Lobban et al (2016). The grids were based on the abundances of Grevesse & Sauval (1998).…”
Section: Spectral Analysismentioning
confidence: 99%
“…While case (i) provides us with a spectrum totally free from the uncertainties arising from long-term spectral variability, case (ii) affords us the highest S/N in a PG 1211+143 spectrum to date, with a combined ∼930 ks of contemporaneous data. Fitting the co-added spectrum is justified on the basis of the long-term X-ray variability being relatively weak > 3 keV (see Zoghbi et al 2015;Lobban et al 2016). All parameters were tied together between spectra except for the relative normalizations.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Given the historical significance of the first AGN UFO observed by XMM-Newton in 2001, and important implications for AGN accretion and galaxy feedback, a more extended observation was carried out on 7 spacecraft orbits over the period June 2 to 2014 July 9, seeking to provide www.an-journal.org greater detail on the spectral and dynamical structure of the outflow. Full details of the XMM-Newton observing log and data extraction procedures for the 2014 observation, with a total on-target exposure of ∼ 650 ks, are given in Lobban et al (2015), reporting a detailed timing analysis.…”
Section: Confirmation Of the Highly-ionized High Velocity Wind In 2014mentioning
confidence: 99%